Detecting a Sinistral Transpressional Deformation Belt in the Zagros - Mohammad Ali Ghanbarian (Geosciences, 2021)
The oblique collision between the northeastern margin of the Arabian platform and the Iranian microcontinent has led to transpressional deformation in the Zagros orogenic belt in the central part of the Alpine–Himalayan orogenic belt. Although previous articles have emphasized the dextral sense of shear in the Zagros orogenic belt, in this paper, using several indicators of kinematic shear sense upon field checking and microscopic thin-section studies, evidence of the development of a sinistral top-to-the NW deformation belt is presented. The mean attitudes of the foliations and lineations in this belt are 318°/55°NE and 19°/113°, respectively.